2013
DOI: 10.1007/s00299-013-1474-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylation alters Arabidopsis root growth in response to auxin via PIN1 degradation

Abstract: Our results showed the histone deacetylase inhibitors (HDIs) control root development in Arabidopsis via regulation of PIN1 degradation. Epigenetic regulation plays a crucial role in the expression of many genes in response to exogenous or endogenous signals in plants as well as other organisms. One of epigenetic mechanisms is modifications of histone, such as acetylation and deacetylation, are catalyzed by histone acetyltransferase (HAT) and histone deacetylase (HDAC), respectively. The Arabidopsis HDACs, HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In addition, we found that TSA and NaB suspended pollen germination and tube growth in a concentration-dependent manner. This is identical to a previous report showing that TSA and NaB significantly inhibited primary root elongation in an approximate negative correlation to TSA and NaB concentration [ 21 ]. These results suggest that HDAC is closely linked to the cellular processes in pollen germination and pollen tube growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that TSA and NaB suspended pollen germination and tube growth in a concentration-dependent manner. This is identical to a previous report showing that TSA and NaB significantly inhibited primary root elongation in an approximate negative correlation to TSA and NaB concentration [ 21 ]. These results suggest that HDAC is closely linked to the cellular processes in pollen germination and pollen tube growth.…”
Section: Discussionsupporting
confidence: 91%
“…We also examined the impact of NaB, another HDAC inhibitor [ 21 ]. As shown in Fig 2 , pollen germination and tube growth were inhibited ( Fig 2 ) after 24 h of treatment, similar to the effect of TSA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the chromatin modifiers may also regulate hormone signaling and pathways [47]. It has been shown that HDAC inhibitors repress the auxin distribution and accumulation in the root apex by promoting the PIN-FORMED 1 (PIN1) protein degradation [50,51], indicating a crosstalk between phytohormones and HDACs in plants. Together, our results highlight that G. hirsutum HDACs may play an important role in fiber development via phytohormones' dependent and/or independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, although HDTs contain a zinc binding domain, it has not been demonstrated that their activity is targeted by TSA. Furthermore, other studies show that application of TSA inhibits root growth and triggers QC divisions (Nguyen et al, 2013;Pi et al, 2015). To determine whether TSA could target HDT1/2, we compared the effect of TSA on QC cell division in the wild type and hdt1,2i-1.…”
Section: Discussionmentioning
confidence: 99%